Incidente de desconsideração da personalidade jurídica - Ludmer, Sérgio (2016)
This paper has the purpose of assessing the normative framework relating to the Disregard doctrine (piercing/lifting the corporate veil) brought by the new Code of Civil Procedure, with an emphasis on the procedural guarantees. We assessed the fundamentals pertaining to the legal entity, the basis for its piercing/lifting and the legislative evolution of its adoption by the Brazilian legal system. We also assessed the procedural principles and guarantees underlying the disregard doctrine, evaluating important procedural matters of the application of such doctrine. Finally, we assessed how one can apply for piercing/lifting the legal entity as provided by the new code of civil procedure and its application in other areas of the Law.